Present status of conservation and management of sea turtle in Cox’s Bazar district, Bangladesh - Hossain, M.A.; Mahfuj, M.S.E.; Rashid, S.M.A.; Ahsan, M.N. (Mesopotamian Journal of Marine Sciences, 2022)
The study was conducted to know the present status of conservation and management of sea turtle in Cox’s Bazar district, Bangladesh. Two species of sea turtles have been making nest in Bangladesh. A total of 251 turtle individuals were found. The highest nesting frequency of Olive ridley (108) and Green turtles (10) were observed in February. About 21,942 hatchlings were produced and released by the hatcheries for conservational step. A total of one hundred people were selected randomly for taking interview to assess their knowledge and attitude towards sea turtle conservation and management. Most of the respondents were fishermen (55%), student and housewife were 20% and 8%, 5% were found involving in business and rest 12% were involved in others activities. About 45% of the respondents thought that turtles were beneficial while other 40% of the respondents thought turtles were harmful. The rest of the respondents (15%) answered that they were not sure whether sea turtle was beneficial or harmful. Most of the fishermen did not know about Turtle Excluder Devices (TEDs) or its uses. It was found that the nesting of sea turtles was reducing and there was lack of knowledge among the people of the study area about the importance of sea turtle conservation and management.